2011
DOI: 10.1080/03602559.2010.543743
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic and Dynamic Mechanical Properties of Extruded Cobalt Ferrite-Polypropylene Composites

Abstract: Cobalt ferrites of 0-45 wt% were incorporated in polypropylene by the extrusion technique. With increasing magnetic loading, the magnetizations were linearly increased according to the rule of mixture and the electrical permittivity was also proportional to the loading as described by Wagner's equation. The magnetic permeability may be increased but was reduced to minimal at high frequencies because of the substantial coercive field of cobalt ferrites after the extrusion. Without considerable adsorption of pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 24 publications
1
12
1
Order By: Relevance
“…This indicated that regular order chains in CoFe 2 O 4 -filled PP could also take place. The endotherms found for these filled samples, however, exhibited smaller magnitude (peak areas) when the amounts of CoFe 2 O 4 powders increased from 5 to 45 % (Table 1), due to the magnetic clusters in PP samples, as seen by SEM in [4]. They may inhibit the formation of order structures during sample preparation since they are embedded into the interchain spacing.…”
Section: Resultsmentioning
confidence: 75%
See 4 more Smart Citations
“…This indicated that regular order chains in CoFe 2 O 4 -filled PP could also take place. The endotherms found for these filled samples, however, exhibited smaller magnitude (peak areas) when the amounts of CoFe 2 O 4 powders increased from 5 to 45 % (Table 1), due to the magnetic clusters in PP samples, as seen by SEM in [4]. They may inhibit the formation of order structures during sample preparation since they are embedded into the interchain spacing.…”
Section: Resultsmentioning
confidence: 75%
“…They may inhibit the formation of order structures during sample preparation since they are embedded into the interchain spacing. As a result, the nucleation of order chains become more difficult in the samples with heavier loading which explains the change in dynamic mechanical properties [4], and may To test this hypothesis, we systematically conducted DSC tests to the semi-crystalline polar polymer, PU. Thermogram of a PU sample without CoFe 2 O 4 displayed the endothermic peak, accounted for the melting of the order portion of chain segments, with a peak position at about 170°C (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations